2014
DOI: 10.1142/s0129167x14500670
|View full text |Cite
|
Sign up to set email alerts
|

The moduli of representations with Borel mold

Abstract: The author constructs the moduli of representations whose images generate the subalgebra of upper triangular matrices (up to inner automorphisms) of the full matrix ring for any groups and any monoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Theorem 2.10 ( [12]). There exists a fine moduli scheme Ch n (Γ) B separated over Z associated to the sheafification EqB n (Γ) of the following functor with respect to Zariski topology:…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…Theorem 2.10 ( [12]). There exists a fine moduli scheme Ch n (Γ) B separated over Z associated to the sheafification EqB n (Γ) of the following functor with respect to Zariski topology:…”
Section: Preliminariesmentioning
confidence: 99%
“…In [12] we have introduced the notion of mold. A mold is, so to say, a subalgebra of the full matrix ring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they are of great importance in the representation theory over schemes, it is difficult to analyze them. To overcome this difficulty, the first author introduced representations with Borel mold and studied the representation variety and the character variety of representations with Borel mold in [19]. Furthermore, we studied the topology of these moduli spaces of representations with Borel mold for free monoids over the field C of complex numbers in [21].…”
Section: Introductionmentioning
confidence: 99%
“…The character variety Ch 2 (m) * is defined as Ch 2 (m) * = Rep 2 (m) * /PGL 2 . In [18], [19], and [20], the first author showed that Ch 2 (m) * is a universal geometric quotient of Rep 2 (m) * by PGL 2 for * = air, B, ss, u, sc. (For * = u, we need to divide Rep 2 (m) u into two parts: the Z[1/2]-part and the F 2 -part.…”
Section: Introductionmentioning
confidence: 99%